2015
DOI: 10.1017/s0007114515003700
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and food sources of choline in European populations

Abstract: Choline is an important nutrient for humans. Choline intake of the European population was assessed considering the European Food Safety Authority European Comprehensive Food Consumption Database and the United States Department of Agriculture Nutrient Database. Average choline intake ranges were 151-210 mg/d among toddlers (1 to ≤3 years old), 177-304 mg/d among other children (3 to ≤10 years old), 244-373 mg/d among adolescents (10 to ≤18 years old), 291-468 mg/d among adults (18 to ≤65 years old), 284-450 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 19 publications
7
88
1
4
Order By: Relevance
“…The reported median energy-adjusted total choline intake was lower than the recommended 276 intake [4,10]. This is in accordance with observational data from European [48,49], North-…”
supporting
confidence: 88%
“…The reported median energy-adjusted total choline intake was lower than the recommended 276 intake [4,10]. This is in accordance with observational data from European [48,49], North-…”
supporting
confidence: 88%
“…The underlying mechanisms are unclear but could involve enhanced adult neurogenesis in the hippocampus or increased release of acetylcholine from neurons of the hippocampus. Dietary intake of choline is now known to be marginal in many European adolescents and is therefore a public health concern (37). Identification of novel factors that can improve academic achievement in children is of great interest to parents, neuroscientists, and society in general.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in the EFSA opinion on Dietary Reference Value on choline (EFSA NDA Panel, ), the mean choline intake estimates in adults ranged from 269 to 468 mg/day from national surveys in seven EU countries (Vennemann et al., ), and were between 265 and 415 mg/day in three studies conducted in non‐EU countries (Chu et al., ; USDA, ; Mygind et al., ). That opinion also reported that in children aged 10–17 years, the choline intake estimate ranged between 244 and 373 mg/day based on seven surveys in EU countries.…”
Section: Assessmentmentioning
confidence: 91%